Теоретично-методологічні підходи до комплексної оцінки фінансового стану підприємства - Соколова, Л. В.; Бакаєва, О. М. (ХІБС УБС НБУ, 2008)
У роботі обґрунтовано роль і місце показників комплексної оцінки фінансового стану підприємства. Визначено нові підходи до вдосконалення діючих методик оцінки фінансового стану. Досліджено методичні проблеми комплексної оцінки фінансового стану і запропоновано напрямки їх вирішення. Розроблено сучасну методику комплексної оцінки фінансового стану, пристосовану до ринкових умов господарювання вітчизняних підприємств. In work methodological approaches are considered and procedure of a complex estimation of a financial condition of the enterprise is generalized. Methods with use of an individual, generalizing and complex estimation of a financial condition are offered. For the purpose of maintenance integrated approach of formation of system of indicators of a financial condition use of the matrix form of granting of the initial financial information is offered. Creation of uniform methodological base of an estimation of a financial condition of the enterprise is the important tool at acceptance of administrative decisions.
Keywords: фінансовий стан; комплексна оцінка; financial state; complex estimation